PENGGABUNGAN DUA GENRE TARI KE DALAM BENTUK KAKEBYARAN - Putu Angga Pratama; I Ketut Sariada; I Nyoman Cerita (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2021)
Kebyar Jang is a dance creation originating from Truna Jaya Dance and Rejang Sacred Lanang Dance. The two dance genres have different characteristics and movement patterns, then the creators combine them to produce a new dance creation using a theme of spirit combination. The purpose of the creation of the Kebyar Jang dance is to preserve and introduce the arts in the Buleleng area, especially dance.This dance creation uses the angripta-sasolahan method by I Kt. Suteja with stages: ngarencana, nuasen, makalin, nelesin and ngebah. Ngarencana is done by observing, thinking, and imagining the creative resources used. Nuasen is a ritual ceremony before improvising the movement by performing prayers followed by all the dancers. Makalin is done by selecting the supporting the elements of creation and improvising the motion. Nelesin is a stage of formation which is done by summarizing the results of improvised motion that have been obtained. Ngebah is the first stage of the performance to find out the form of creation and get the results of the evaluation. Using the theory of imagination, symbols and aesthetics to assist in the creation process.This dance creation is packaged in the form of the kakebyaran dance which is danced by 6 male dancers using a fan property. Using makeup and clothing a combination of the rejang dance and the kakebyaran dance. Accompanied by the gamelan Semarandhana that can support the atmosphere of each structure that is displayed.Keywords: Kebyar Jang, Kakebyaran Dance, Truna Jaya Dance, Rejang Sacred Lanang Dance.